Judicial Activism in Brazil”S Constitutional Court?: Studies in the Recognition of Brazilian Indigenous Tenure rights - Anna Lucia Berardinelli (Faculty of law Udayana University, 2017)
Small part of entire Brazil’s national territory has already been demarcated as indigenous land. Facts reveal that the Natives were killed because of land issues, indicating that land issues and tenure rights are the epicenter of the problem. This article focuses on the cardinal point of Brazilian legal debates: keeping indigenous people’s tenure over the land they have been occupying immemorially. The analysis explores normative aspects on constitutional and legal protection over Brazilian indigenous rights and further scrutinizes the relevant case law that was settled before the Brazil’s Constitutional Court. Keywords: Brazil, Indigenous, Constitution, Court.